Solution-processed photodetectors - Chourasia N.K.; Pal B.N. (My University, 2025)
Efficient detection of the light of electromagnetic waves has enormous applications in modern science and technology. Commercial photodetectors (PDs) are commonly made of crystalline inorganic materials such as Si and III-V compound semiconductors. However, solution-processed semiconductors such as organic polymers, colloidal quantum dots (QDs), metal chalcogenides, and metal-halide perovskites have shown great potential in the fabrication of efficient PDs at a significantly lower cost with a higher yield. These solution-processed PDs can combine ease of processing, tunable optoelectronics property, and their compatibility with flexible substrates. Based on the nature of semiconducting materials, these PDs can detect different ranges of the spectrum of light such as ultraviolet (UV), visible (Vis), and infrared (IR), which are commercially known as UV, Vis, and IR detectors, respectively. Again, based on the range of their sensitivity, PDs can be classified as broadband or narrowband PDs. All of these different classes of PDs have applications in different areas of electronics. In this chapter, we discuss the device architecture and parameters of PDs, different types of solution-processed semiconductor-based PDs, their applications, advantages, and prospects. © 2021 Elsevier Inc. All rights reserved.